eCall++: an enhanced emergency call system for improved road safety - Blancou, Jon
This paper presents an enhanced emergency Call (eCall) system that combines the native eCall services with the benefits provided by vehicular communications networks. The proposed solution, named eCall++, consists of a mobile application that automatically detects an accident and disseminates the alert notification, both via eCall and vehicular communications standards (IEEE WAVE / ETSI ITS-G5). In this work, two additional services are introduced: a passenger detection algorithm that informs the emergency services about the number of people inside the car during the crash; and a video streaming mechanism that enables vehicles in the vicinity of the accident to send a live record of the accident scene. These features are developed and implemented on an Android device connected to a custom vehicular communications system (the IT2S platform). The experimentally obtained results validate the proposed system and provide viable evidence to add additional features to the conventional eCall architecture.